Hubungan Strategi Coping dengan Kualitas Hidup Caregiver yang Merawat Pasien Skizofrenia di Poliklinik Rumah Sakit Jiwa Aceh - Maulid Hidayatun; Urip Pratama; Nurul Amna (Lembaga Pengembangan Kinerja Dosen, 2025)
The long-term care required by schizophrenia patients places a heavy burden on caregivers who are responsible for meeting the patients' needs. Performing these caregiving tasks often causes physical and emotional stress on caregivers, especially due to the long-term nature of the care. In situations like this, coping strategies play a crucial role in supporting the well-being of caregivers so that they are able to face the challenges that arise during the process of caring for schizophrenic patients. This study focuses on examining the correlation between coping strategies and the quality of life of caregivers who provide care for schizophrenic patients at the Aceh Mental Hospital Polyclinic. The research design applied was analytical with a cross-sectional approach. A total of 115 caregivers were sampled through accidental sampling from a total population of 4,035 families. Research data were collected using two measuring instruments, namely the Brief COPE questionnaire and The Schizophrenia Caregiver Quality of Life Questionnaire (SCGQoL). The research process took place at the Aceh Mental Hospital Polyclinic from March 6 to 24, 2025. Data analysis used univariate and bivariate methods. Based on the research results, it was found that 108 caregivers (93.9%) were in the low coping strategy category, while 80 caregivers (69.6%) had a moderate quality of life. Statistical testing with Chi-Square produced a p-value of 0.001, which indicates a significant relationship between coping strategies and the quality of life of caregivers. Therefore, it is hoped that health care institutions can improve mental health nursing interventions for patients' families, particularly through educational programs on managing schizophrenia patients at home and assistance in identifying adaptive coping resources for patients' families.